Adjunct Intravitreous Triamcinolone Acetonide in the Treatment of Diabetic Macular Edema with Anti-VEGF Agents - Robert B. Garoon; Robert E. Coffee; Lai Jiang; Christina Y. Weng; Petros E. Carvounis (Journal of Ophthalmology)
Aims. To compare visual and anatomic outcomes of adjunct intravitreous (IVT) triamcinolone acetonide to antivascular endothelial growth factor (VEGF) injections to IVT anti-VEGF injections alone for center-involving diabetic macular edema (DME) in treatment-naïve eyes. Methods. Retrospective study of treatment-naïve eyes with center-involving DME. The primary outcome was the change in best corrected visual acuity (BCVA) in eyes receiving only IVT anti-VEGF (group 1) and eyes receiving IVT anti-VEGF and adjunct IVT-TA (group 2). Results. Included were 192 eyes. The mean change in BCVA was +3.5 letters in group 1 compared to −3.5 letters in group 2 (p=0.048). Final macular thickness improved by −94 μm in group 1 versus −68 μm in group 2 (p=0.26). In group 1, 5/150 eyes compared to 9/42 eyes in group 2 (3.3% versus 21%, p=0.0005) had a IOP >10 mmHg increase. Six of 126 phakic eyes in group 1 versus 12/33 phakic eyes in group 2 underwent cataract surgery (4.7% versus 36.3%, p=0.00009). Conclusions. IVT-TA results in no additional benefit in eyes treated with anti-VEGF agents for DME.